Economic Benefits and Integrated Coastal Management Sustainability - Pomeroy, Robert S.; Oracion, Enrique G.; Caballes, Demberge A.; Pollnac, Richard B. (Silliman Journal, 2022)
This paper will examine the factors influencing the sustainability of integrated coastal management (ICM) projects in the Philippines, specifically in two locations, Bais Bay area of Negros Oriental Province and Mabini-Tingloy (known as Anilao) area of Batangas Province, where a number of ICM projects have been implemented since the mid-1980s. Indicators for ICM project impacts are developed and analyzed to determine their relationships with ICM project sustainability. Years of residency in the community, participation in 1CM projects with resource management and enterprise/alternative livelihood activities, and the total number of projects participated in were the strongest predictors of perception of ICM project sustainability at the two sites in the Philippines. Participation of community members in the 1CM project design and implementation and real or perceived economic benefits from the project influence participants to sustain project activities after project completion.